Critical Analysis of Foundational Challenges in Modern Healthcare Systems - Alharbi, Omar Rasheed S; Alhrbi, Bandar Shathian Motlq; Al-Rashidi, AbdulGhani Mubarak Hamad; Alzabni, Abdullah Shuwayman Mohammed; Al Harbi, Abdullatif Fahd Abdullah; Alharbi, Abdullah Sulaiman Mufrah; Al Harbi, Abdulsalam Fahd Abdullah; Alhomiani, Ahmad Hamdan Fahad; Al Harbi, Yousef Sahoud Maoala; Alfuraydi, Fawaz Saad Mater (Journal of Ecohumanism, 2024)
The various components of the present-day healthcare delivery system are multidimensional and require a vigorous response to the request for effective healthcare delivery, management and direction of healthcare workers, and formulation of policies and strategies on the use of technology, among others. This paper examines a few of the foundational issues all healthcare systems experience, which stifle their efficiency as healthcare advances. This paper critically evaluates the following significant challenges facing twenty-first-century healthcare: Workforce Challenges, Service Delivery, Financial Viability and Technological Incorporation. Based on the effects of these challenges on the quality and availability of health services, this paper provides solutions to these challenges to enhance the quality of health care around the globe. Recent and case studies are explored, and their findings are described to provide an overall view of these problems and their possible solutions.